Before Rice and the First Rice: Archaeobotanical Study in Ha Long Bay, Northern Vietnam - Wang, Weiwei; Nguyen, Kim Dung; Dang Le, Hai; Zhao, Chunguang; Carson, Mike T.; Yang, Xiaoyan; Hung, Hsiao-chun (Frontiers in Earth Science, 2022)
Mainland Southeast Asia experienced a long, sustained period of foraging economy before rice and millet farming spread into this area prior to 4000 years BP. Although hundreds of individuals from dense cemeteries are found in several hunter-gatherer sites in Guangxi, Southern China, and Northern Vietnam, dating from the early to middle Holocene (ca. 9000˗4500 years BP), so far, little has been known about food sources in these pre-farming contexts. In particular, plant food resources have been unclear, although they likely were crucial to supporting rather large populations of hunter-gatherers in this region. To investigate this issue, micro plant remains, including starches and phytoliths, were recovered from stone tools excavated at the Cai Beo site in Ha Long Bay of coastal Northeastern Vietnam, and those findings revealed new understanding of the ancient diet. Examinations of those residues indicated that the hunter-gatherers at Cai Beo as early as 7000–6000 years BP exploited a broad spectrum of plants, such as taros, yams, acorns, palms, and more. This study exemplifies how maritime hunter-gatherers interfaced with the local plants and generated population growth from about 7000 to 4500 years BP. The results help us to conceptualize the early exploitation, management, and potential cultivation of subtropical and tropical plants over the broad geography of Asia and the Pacific before the arrival of rice and millet farming. In particular, the result validates the significance of roots and tubers in the ancient subsistence economy of Southeast Asia. Moreover, from the archaeological context of 4500 to 4000 years BP, the rice discovered in this study represents one of the earliest known in Mainland Southeast Asia.